Isolation and Screening of Surfactant-producing Bacteria from Indonesian Marine Environments and Its Application on Bioremediation - Susilaningsih, Dwi; Okazaki, Fumiyoshi; Yopi, Yopi; Widyastuti, Yantyati; Harayama, Shigeaki (ANNALES BOGORIENSES, 2013)
Isolation and screening have been undertaken on oil-degrading microbes from Indonesian marine environments. During screening process it has been found many bacterial isolates capable of degrading crude oil. Hence, study has been focused on the biodiversity of biosurfactant-producing bacterial species in Indonesian marine environment and its function for remedial the pollutant in marine and soil areas. A total of 103 out of 463 isolates showed positive surfactant-degrading properties. By means of partial 16S rRNA gene analyses, it has been found that the majority of taxa are related to Alcanivorax, Pseudomonas, Bacillus, Bortetela, Brucella, Acenitobacter, Staphia, Lysobacter, and Talasosophira. Biosurfactant properties assay showed that they were capable of lowering the surface- and interfacial water tension from 74 mN/m to 40-65 mN/m and from 24 mN/m to 6-10 mN/m, respectively. In addition, most of the surfactants were capable of emulsifying hydrocarbon (crude oil) of 0.01 to 0.15 units, comparable to 0.08 units of synthetic surfactant (20% Tween). Further observation showed that the majority of the surfactants were able to degrade a long chain of alkane, but not branched alkane, with a recovering rate of 20-80%. The application of the surfactant towards oil polluted model beach was done in laboratory scale and showing the surfactant obtained from microbial broth cultures capable for recovering the oil pollutant significantly, compared to the control (without addition microbial broth). Â